Business Plan - ThirdEye.com - Haupt Buchenrode, Ursula (2009)
Consider a market of 18 million people with an annual growth rate of 7%, which is expected to increase up to 28 million by 2020 . Combine this with the social networking world, one of the most popular online categories in Brazil, with a penetration of 84.3% of the online Brazilian audience which is one of the highest in the world . The result is The Third Eye, a business that tackles a growing social gap through a profitable business model that engages different agents of the society.